Power and influence of islam-based political parties in Bangladesh: perception versus reality - Jahan, Ferdous; Shahan, Asif M (© 2013 SAGE Publications Ltd, 2016)
This article was published in the Journal of Asian and African Studies [© 2013 The Author(s) ] and the definite version is available at :http://dx.doi.org/10.1177/0021909613488350 The Journal's website is at: http://journals.sagepub.com/doi/10.1177/0021909613488350